Raúl Ruiz, Poetics Of Cinema And “Intentionality”: Unworking The Soul’s Standardization Against The Government Of The Living. (Periphērica, 2025)
The poetics of cinema by filmmaker Raúl Ruiz, as read by Chilean philosopher Willy Thayer, can be understood as an infrapolitical critique of the biopolitics (government of the living) that is at play in the cinema-spectator relationship and its determination by the old Christian-theological apparatus of “intentionality” (soul-world relationship): a body subject to the form (law, word, image, “mask”) that turns it into a “person” and whose unity depends on the unity of the world as the order of words, things, and events—a unitary order guaranteed by a theological author and meta-reader in pure act—and the insemination of that order into the perceptive, intellectual, and practical “soul.”